(untitled) (International Journal of Physiology, 2024)
Background: Contemporary concerns recognize atmospheric air pollution as a significant contributor to cardiovascular diseases. Notably, wood dust, colloquially known as sawdust, emerges as a source of air pollution. Our investigation sought to assess the impact of wood dust on the cardiovascular health of carpenters in the Dakar region. Methods: This cross-sectional study encompassed one hundred (100) carpenters in the Dakar region. A comprehensive questionnaire gathered data on socio-demographic features, professional experience, medical history, preventive measures, and lifestyle habits. Vascular function assessment involved determining finger-toe pulse wave velocity (ft-PWV) using a popmeter. Additionally, we screened for obliterative arteriopathy of the lower limbs (OALL). Heart rate variability measurement provided insights into the sympatho-vagal balance of nervous control over cardiac activity. Results: The average age in our population was 38 ±7.2 years, with a body mass index of 22.7 ±2.8 kg/m2. A majority (69%) worked an average of 10.2 hours per day for six days per week. Approximately 73% of the shops were observed to be enclosed. Respiratory and ocular symptoms were prevalent among participants. Analysis using the Pop meter revealed arterial stiffness (ft-PWV>10 m/s) in 3% of participants, and 11% exhibited arterial hypertension. OALL was present in 8% of participants. Furthermore, a positive correlation (P=0.003; r=0.581) between ft-PWVV and mean arterial pressure was noted. Data on cardiac variability indicated a substantial proportion of participants displaying decreased tone in the cardiac-parasympathetic nervous system in the supine position (94.73% had RMSSD values above norms). Notably, abnormal activation of the parasympathetic system (HF) and decreased sympathetic system activity (low values for HF, LF, and LF/HF compared with norms) were observed in the orthostatic position. Conclusion: Carpentry work in environments with elevated air pollution, potentially emanating from wood dust, poses inhalation risks for workers. The inhalation of wood dust appears linked to an increased risk and exacerbation of cardiovascular complications.